The effect of implant design on the stress distribution in a three-unit implant-supported distal cantilever fixed partial denture: A three-dimensional finite-element analysis - Pradeep Koka; Abhijita Mohapatra; Ponsekar Abraham Anandapandian; K Murugesan; M Vasanthakumar (Wolters Kluwer Medknow Publications, 2012)
Context: Implant design influences the stress distribution in an implant-supported distal cantilever fixed partial denture and supporting bone tissue. Aim: The purpose of this study was to investigate the effect of implant design on the stress distribution in the framework, implant, and surrounding bone, using a three-dimensional finite-element analysis. Materials and Methods: A three-dimensional finite-element model of a mandibular section of bone with implants placed in the first and second premolar region was created to support a distal cantilever fixed partial denture. A one-piece and two-piece implant and its suprastructure were simulated into wire frame models using Pro engineer (Pro E) program. Four models were created in this study. Results: Comparative analysis of all models showed that the maximum stress overall was in the cervical portion of the secondary abutment. When used in combination, the maximum stress was when the two-piece implant was used as secondary abutment. The one-piece implant showed less stress compared to its counterpart when used as secondary abutment. The maximum stress distribution in the bone was around the neck region of the secondary implant. Conclusion: Within the limitations of this study, it can be concluded that stress distribution is better in a one-piece implant design when compared with the two-piece implant design, with stress concentration being more at the junction of the abutment and the implant fixture in the two-piece implant. When implants are used as abutments (either primary or secondary), irrespective of their position and design, the secondary implant shows the maximum amount of stresses.